Study of Electrical Properties of Silver Nanoparticles on Porous Silicon - Mohammed alsaalihiu; Ghazwan Al Nuaimi (College of Education for Pure Sciences, 2021)
In this paper, porous silicon has been prepared and studied by photochemical etching method using a n-type silicon wafer with electrical resistivity (0.01-0.02 Ω.cm), orientation (100), hydrofluoric acid of 20% HF, current density of 15 mA / cm2 and etching time at (5 min). Silver nanoparticles (AgNPs) have been deposited using laser ablation by drop casting with different laser energy of 400,600 and 800m J. The electrical properties (I-V measurements) of silver nanoparticles on porous silicon have studied in both light and dark conditions. It can be seen the samples behave a rectifier and the current density increases with increase laser energy due to increase in concentration of silver nanoparticles, which lead to a decrease in the values of resistivity as the laser energy increases, this is attributed to the pores are filled with silver nanoparticles and lead to interference between silver and the porous silicon layer. The silver nanoparticles play an important role in forming a homogeneous layer and enhancing the crystal stability of the porous silicon layer.